ARITHMETIC IN EXCEL: MICROSOFT’S SILENCE ON GLOBAL EDUCATION - Gonçalves, Rafael Alberto (Seven Editora, 2025)
Licensed Microsoft Excel is one of the most widely used tools in the world for calculations, financial analysis, and data manipulation. Despite its apparent precision, Excel is not infallible. There are situations where it can present arithmetic errors, especially due to internal limitations of numerical representation, rounding, and the peculiarities of its formulas. Understanding these factors is essential to avoid flawed conclusions in critical spreadsheets. Using a practical example, this article discusses the pedagogical implications of a multiplication error in Excel, highlighting how recurring inaccuracies can compromise mathematics education. Such flaws can seriously harm data analysis, leading to incorrect interpretations and decisions. Excel uses floating-point representation based on the IEEE 754 standard to store decimal numbers, which can prevent the accuracy of certain values. Although this phenomenon is not exclusive to Excel, its widespread adoption makes the effects more noticeable. For example, operations like 0.1 * 0.2 can result in 0.20000000000000004 instead of 0.2 — a typical inaccuracy of floating-point arithmetic. Although generally not visible in the standard interface, these flaws can affect logical comparisons and chained calculations. In the pedagogical context, similar errors in multiplication operations can compromise the teaching of fundamental mathematical concepts. Errors derived from floating-point representation can occur in various software. In the case of Excel, its widespread adoption and lack of transparency make the impact of these problems even more severe, which accentuates the pedagogical risks of the uncritical use of a tool widely adopted as a reference by students and professionals. DOI: https://doi.org/10.56238/sevened2025.030-041